Adult congenital heart disease: A paradigm of epidemiological change. (1st September 2016) - Ntiloudi, Despοina; Giannakoulas, George; Parcharidou, Despοina; Panagiotidis, Theofilos; Gatzoulis, Michael A.; Karvounis, Haralambos
Abstract: Increasing survival rates for patients with congenital heart disease (CHD) represent a major achievement of modern medicine. Despite incredible progress been made in diagnosis, follow-up, early treatment and management in adulthood, many patients are faced with long-term complications, such as arrhythmia, thromboembolism, heart failure, pulmonary hypertension, endocarditis and/or the need for reoperation. In parallel, half of the patients are female, most of childbearing age, and, thus warrant specialist reproductive counseling and appropriate obstetric care. It is not surprising therefore, that healthcare utilization has steadily increased for CHD in recent years. Furthermore, cardiology and other medical disciplines are now faced with new challenges, namely the provision of expert care and optimal, lifelong medical surveillance for these patients. Highlights: Epidemiology of congenital heart disease has radically changed. Many patients are faced with long-term complications. Αppropriate lifelong medical surveillance for ACHD patients is imperative.